Improving the Segmentation of Colorectal Cancer from Histopathological Images Using a Hybrid Deep Learning Pipeline: A Case Study - Fahima Idiri; Farid MEZIANE; Hakim BOUCHAL (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2026)
Early and precise diagnosis of colorectal cancer plays a crucial role in enhancing patients' outcomes. Although histopathological assessment remains the reference standard for diagnosis, it is often lengthy and subject to variability between pathologists. This study aims to develop and evaluate a hybrid deep learning-based approach for the automated segmentation of Hematoxylin and Eosin-stained colorectal histopathology images. The work investigates how preprocessing strategies and architectural design choices influence the model’s ability to identify meaningful tissue patterns while preserving computational efficiency. Furthermore, it demonstrates the integration of a deep learning-based segmentation module into colorectal cancer diagnostic workflows. Several deep learning–based segmentation models with varying architectural configurations were trained and evaluated using a publicly available endoscopic biopsy histopathological hematoxylin and eosin image dataset. Preprocessing procedures were applied to generate computationally efficient image representations, thereby improving training stability and overall segmentation performance. The best-performing configuration achieved a segmentation accuracy of 0.97, reflecting consistent and reliable performance across samples. It accurately delineated cancerous tissue boundaries and effectively distinguished benign from malignant regions, demonstrating sensitivity to fine morphological details relevant to diagnosis. Strong agreement between predicted and expert-annotated regions confirmed the model’s reliability and alignment with expert assessments. Minimal overfitting was observed, indicating stable training behavior and robust generalization across different colorectal tissue types. In comparative evaluations, the model maintained high accuracy across all cancer categories and outperformed existing state-of-the-art approaches. Overall, these findings demonstrate the model’s robustness, efficiency, and adaptability, confirming that careful architectural and preprocessing optimization can substantially enhance segmentation quality and diagnostic reliability. The proposed approach can support pathologists by providing accurate tissue segmentation, streamlining diagnostic procedures, and improving clinical decision-making. This study underscores the value of optimized deep learning models as intelligent decision-support tools for efficient and consistent colorectal cancer diagnosis